An Islamic Perspective on Governance - Hassan, Abul (International Journal of Shari'ah and Corporate Governance Research, 2020)
BOOK REVIEWAN ISLAMIC PERSPECTIVE ON GOVERNANCE, By Zafar Iqbal and Mervyn K. Lewis, Cheltenham (UK) and Northampton, MA(USA): Edward Elgar Publishing Limited, 2009, Pp. xvi + 368. ISBN 978 1 84720 138 6